GAMBARAN KEHIDUPAN TOKOH KIYOHA SEBAGAI YŪJO PADA ZAMAN EDO DALAM FILM SAKURAN KARYA SUTRADARA NINAGAWA MIKA - TRIVIAN ARDITYANTI, FRANSISCA ROMANA (Jurnal Ilmiah Mahasiswa FIB, 2013)
In this paper the author examines the life of yūjo in Yoshiwara in Edo Erathat is described on Sakuran film. At that time, prostitution was not a taboo thing,that make this business grew rapidly. To make everything under firm control, thegovernment built special area for entertainment and prostitution in Edo, namedYoshiwara. Yoshiwara also became resident and work place for comfort woman,yūjo. The problem in this study is: how the life of Kiyoha as a yūjo in Edo Era. This research use sociology literature aaproach, character andcharacterization, and mise-en-scene to analyze the life of yūjo in Yoshiwara inEdo Era. The study shows that yūjo is devided into five classes, kamuro, shinzo,zashikimochi, yobidashi chūsan, and oiran. The classification is based on yūjo’sskill and popularity. Along with status going up, the performence will change.The main jobs of yūjo are to entertain and satisfy the sexual desire of clients. Tomanage the yūjo, the firm make regulation in Yoshiwara and every brothels. Ifthey broke the rules, they will get some hard punishment. Next research, author suggest to use this film with semiotic approach toenrich the literature. Keyword: sakuran movie, yūjo, yoshiwara, edo era